Strategi pemasaran sapi potong di PT Tunas Jaya Raya Abadi Nganjuk - Jaisy Aghniarahim Putritamara; Nanang Febrianto; Poespitasari Hazanah Ndaru (Jurnal Ilmu-Ilmu Peternakan, 2018)
This research conducted in PT. Tunas Jaya Raya Abadi Nganjuk. The objectives of this research were obtain a better understandin internal as well as exsternal environmental condition, secondly trying to covering the formulate the marketing strategi. Method that used in this research was a survey method, it contains observation, interview, and documentation. The data analyzed by SWOT analysis. The result showed internal strategy factors matrix give positive value where it strengths were stronger than it weakness (S = 2,29>W = 0,71). External strategy factors’ matrix also give positive value where it opportunities values were bigger than it threats values (O = 1,84 > T = 0,70). From the result, we know that environmental condition in PT. Tunas Jaya Raya Abadi was very good, and gave good prospect for its progress in the future. It known from total score of strength and opportunities factors (SO = 4.13). From SWOT analysis, strategy that will be taken was in the first quadrant where internal and external factors were positive. In general terms, it means that the environmental condition of PT. Tunas Jaya Raya Abadi, relatively has bigger opportunity than its weaknesses. The decision that made by PT. Tunas Jaya Raya Abadi for marketing strategy was rapid strategy by which all opportunity could be captured as marketing consideration.